Kedudukan Pejabat Sementara Notaris dalam Hal Notaris Diberhentikan Sementara dari Jabatannya - Pradnyana, Komang Teja; Mertha, I Ketut (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 6 No 02 (2021)DO - 10.24843/AC.2021.v06.i02.p12, 2021)
Abstract The purpose of this writing is to determine the ratio legis for the position of Temporary Notary Officer in the event that the Notary is temporarily suspended from his/her position and to understand the reformulation of the regulation of the position of the Notary's Temporary Officer in the event that the Notary is temporarily suspended from his/her position. The research method used is the normative research method, which departs from the absence of norm on the regulation of the position of Temporary Notary Officer in order to carry out the position of a temporarily suspended Notary as stipulated in Article 1 point 2 of the UUJN-Amendment, with a statutory approach and a conceptual approach. The technique of collecting legal material is in the form of card system technique and legal material analysis technique in the form of descriptive technique and construction technique. The research findings are as follows: Ratio Legis for the position of a Notary's Temporary Officer in the event that a Notary is temporarily suspended from his/her position is to maintain the continuity of the Notary's position, even though the Notary (official) cannot carry out his/her duties for a while because of being temporarily suspended, but persist because it is a permanent work sector. Regulatory reformulation of the position of Temporary Notary Officer in the event that the Notary is temporarily suspended from office is by establishing a norm that revises the norm of Article 1 point 2 UUJN-Amendment.   Abstrak Tujuan penulisan ini adalah untuk mengetahui ratio legis kedudukan Pejabat Sementara Notaris dalam hal Notaris diberhentikan sementara dari jabatannya dan memahami reformulasi pengatuan atas kedudukan Pejabat Sementara Notaris dalam hal Notaris diberhentikan sementara dari jabatannya. Metode penelitian yang dipergunakan yaitu metode penelitian normatif, yang beranjak dari kekosongan norma atas pengaturan kedudukan Pejabat Sementara Notaris guna menjalankan jabatan Notaris yang diberhentikan sementara sebagaimana ditentukan dalam Pasal 1 angka 2 UUJN-Perubahan, dengan jenis pendekatan perundang-undangan serta pendekatan konseptual. Teknik pengumpulan bahan hukum berupa teknik sistem kartu dan teknik analisisa bahan hukum berupa teknik deskriptif dan teknik konstruksi. Adapun temuan penelitian adalah sebagai berikut: Ratio legis kedudukan Pejabat Sementara Notaris dalam hal Notaris diberhentikan sementara dari jabatannya adalah untuk mempertahankan keberlangsungan jabatan Notaris itu sendiri, meskipun Notaris (pejabat) tidak dapat melaksanakan tugas jabatannya untuk sementara waktu karena diberhentikan sementara, namun jabatan Notaris harus tetap ada karena merupakan lingkungan pekerjaan tetap. Reformulasi pengaturan atas kedudukan Pejabat Sementara Notaris dalam hal Notaris diberhentikan sementara dari jabatannya adalah dengan pembentukan norma yang merevisi norma Pasal 1 angka 2 UUJN-Perubahan.